Prevalence of serologic markers of transfusion and sexually transmitted infections and their correlation with clinical features in a large cohort of Brazilian patients with sickle cell disease. Issue 2 (5th December 2019) - Blatyta, Paula F.; Kelly, Shannon; Sabino, Ester; Preiss, Liliana; Mendes, Franciane; Carneiro‐Proietti, Anna B.; Werneck Rodrigues, Daniela de Oliveira; Mota, Rosimere; Loureiro, Paula; Maximo, Claudia; Park, Miriam; Mendrone‐Jr, Alfredo; et al.
Abstract : BACKGROUND: Patients with sickle cell disease (SCD) often require red blood cell (RBC) transfusion for clinical complications, so may be exposed to transfusion‐transmitted infections (TTIs). The prevalence of markers for human immunodeficiency virus (HIV), hepatitis C virus (HCV) and B (HBV), human T‐cell lymphotropic virus (HTLV‐1/2), Chagas disease, and syphilis in an SCD cohort in Brazil were studied. STUDY DESIGN AND METHODS: Clinical history, interview data, blood samples, and medical chart review data were collected during cohort enrollment from November 2013 to May 2015. Serologic markers of infection were assessed. Standard measures of statistical association were calculated, and multivariable models were developed for the most prevalent infections to identify associated factors. RESULTS: Infection markers were evident in 5.2% (144/2779) of the enrolled cohort. Anti‐HCV was detected in 69 (2.5%), syphilis antibodies in 34 (1.2%), anti‐HTLV‐1/2 in 17 (0.6%), HBV surface antigen in 13 (0.5%), Chagas disease antibodies in 13 (0.5%), and anti‐HIV in 8 (0.3%) of participants. Factors associated with increased odds of being anti‐HCV reactive were older age, illegal drug use, increasing number of RBCs, more than three pain crises in the previous year, and geographic location. Syphilis was associated with older age, females, and smoking history. CONCLUSION: HCV infection was more common in older patients who may have received RBCs before testing was performed on donations, suggesting possible historic transfusion transmission. The cohort showed decreasing rates of infections and a reduction in transfusion transmission markers in younger patients compared to historical literature except for syphilis, indicating contemporary reduced risk of TTI.